Altered functional brain connectivity in children and young people with opsoclonus–myoclonus syndrome. (23rd September 2016) - Chekroud, Adam M; Anand, Geetha; Yong, Jean; Pike, Michael; Bridge, Holly
Abstract : Aim: Opsoclonus–myoclonus syndrome (OMS) is a rare, poorly understood condition that can result in long‐term cognitive, behavioural, and motor sequelae. Several studies have investigated structural brain changes associated with this condition, but little is known about changes in function. This study aimed to investigate changes in brain functional connectivity in patients with OMS. Method: Seven patients with OMS and 10 age‐matched comparison participants underwent 3T magnetic resonance imaging (MRI) to acquire resting‐state functional MRI data (whole‐brain echo‐planar images; 2mm isotropic voxels; multiband factor ×2) for a cross‐sectional study. A seed‐based analysis identified brain regions in which signal changes over time correlated with the cerebellum. Model‐free analysis was used to determine brain networks showing altered connectivity. Results: In patients with OMS, the motor cortex showed significantly reduced connectivity, and the occipito‐parietal region significantly increased connectivity with the cerebellum relative to the comparison group. A model‐free analysis also showed extensive connectivity within a visual network, including the cerebellum and basal ganglia, not present in the comparison group. No other networks showed any differences between groups. Interpretation: Patients with OMS showed reduced connectivity between the cerebellum and motor cortex, but increased connectivity with occipito‐parietal regions. This pattern of change supports widespread brain involvement in OMS. What this paper adds: The cerebellum shows abnormal functional connectivity with both motor and visual cortices in patients with opsoclonus–myoclonus syndrome (OMS). Patients with OMS showed reduced connectivity between the cerebellum and motor cortex. Patients with OMS showed increased functional connectivity between the cerebellum and the visual cortex. This article is commented on by Gallerini and Marsili on pages14–15 of this issue.